Comunicação, cultura e linguagem: o rádio como instrumento para a prática de educação ambiental na província do Cunene (República de Angola) - Sipandeni, Benedito Lilongeni (2013)
The last four decades of the twentieth century were marked by preoccupation of scholars with environmental degradation and biodiversity loss, mainly due to human action. The need for conservation and preservation of ecosystems that support life on the planet put, since the discussion of environmental issues on the political agenda at local and international level. The speed with which natural resources are exploited mainly in developing countries threatens the biodiversity of those nations attempting to develop at any cost. To mitigate this crisis, spread starting from the 1980s a new model of development, focusing on sustainability. This development is considered as an intra and intergenerational commitment, whereby current generations should use natural resources to meet their basic needs without harming future generations. The idea of sustainable development becomes possible from the time when the population becomes aware of the impacts they cause to the environment that can endanger the ecological balance and their own quality of life. In this case, the media present themselves as educational tools for guidance of the population both in urban and rural centers about environmental problems present there. However, many environmental education strategies are doomed to failure because they are produced from the metropolis, to a heterogeneous audience and without taking into account the differences and realities of each field. This study is an ethnographic research that aims to develop a proposal for environmental education via radio broadcast to the people of Cunene Province (Republic of Angola). It also has the prospect of further implementation in other regions of the country, considering the specific aspects of ethnic, cultural, linguistic, socioeconomic and environmental of each region. Radio was the medium chosen because it is the only one that emits from the Cunene Province and also for its ability to influence change in audience behavior, individually and collectively. WFor this proposal were produced four pilot programs (two Portuguese and two in Oshiwambo - language spoken in southern Angola Province of Cunene and north of the Republic of Namibia), having as target audiences young and adolescent students, speakers of the two languages.